PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING, INQUIRY LEARNING DAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA SISTEM PENDINGIN JURUSAN TEKNIK KENDARAAN RINGAN (TKR) - Tandi Linok, Roni; Hendra Jaya; Muhammad Yahya (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2024)
This study is a type of quasi-experimental research, which aims to examine the influence of applying discovery learning, problem based learning, and inquiry learning models on students' cognitive learning outcomes in Cooling System learning material in light vehicle engineering (TKR). The independent variables in this research are discovery learning, problem based learning, and inquiry learning models, while the dependent variable is students' cognitive learning outcomes. The research sample consisted of three classes selected by using random sampling technique. To discover the influence of applying the learning model, a pre-test was conducted to examine the students' initial knowledge. Then, each class was given learning model treatment. At the end of the lesson, each student was given a post-test to discover the students' learning outcomes. Based on the results of the research, it is discovered that students in the discovery class increase by 73.86 in the post-test from 26.54 in the pre-test, while in the PBL class, students' scores increase by 63.68 in the post-test from 25.06 in the pre-test, and in the inquiry class, students’ score increase in the post-test from 39.91 in the pre-test. The hypothesis testing used in this research was a paired sample test using SPSS. Based on the results of the t test conducted in each class, it shows a t value of 18.345 in the discovery class, a t count of 11.575 in the PBL class, and a t count of 11.556 in the inquiry class. The three classes show t count > t table 1.71 and the result obtained a significance of 0.000 in each class, which means < 0.05. Thus, H0 is rejected and Ha is accepted. So, it can be concluded that there is an influence of the use of discovery learning model, problem based learning, and inquiry learning on students' cognitive learning outcomes in Cooling System learning material in light vehicle engineering.